Methodology for Verification of Geometrically Complex Components Through Reverse Engineering - Peter Gabštur; Marek Kočiško; Jakub Kaščak; Martin Pollák (Applied Sciences)
Verification of geometrically complex components is a crucial step in ensuring the quality and functionality of industrial products. This article presents a comprehensive methodological approach to their verification using reverse engineering techniques. The study highlights the limitations of traditional measurement methods for complex geometries and proposes a framework that integrates advanced 3D scanning and digital modeling. The methodology involves obtaining accurate geometric data, with deviations during repeated measurements being well within the tolerance range. With a tolerance of ±1 mm, the maximum deviation was −0.66 mm, while the maximum deviation with the highest tolerance of 4.5 mm was 1.19 mm. These data were compared with predefined 3D models to analyze deviations and identify process errors. By applying this detailed methodology, more precise fixtures were created, resulting in measurements with deviations well below the required tolerances, compared to measurements without this methodology. A practical example of the design and verification of a welding fixture for cabin manufacturing illustrates the effectiveness of reverse engineering in detecting inconsistencies and optimizing manufacturing processes. The findings emphasize the importance of geometric accuracy in quality control and demonstrate how reverse engineering can streamline verification processes and enhance product reliability. This approach is particularly valuable for the manufacturing industry, which requires high precision in the production of geometrically complex components.